SELECTION OF PEACH VARIETIES SUITABLE FOR THE CONDITIONS OF ANDIJAN REGION - Islamov Sokhib Yakhshibekovich; Xatamova Xamidakhon Komiljonovna (Western European Studies, 2025)
The article presents the results of a study conducted in the conditions of the Andijan region, identifying the highest yield per unit area among 6-year-old peach varieties. Among the fuzzy peach varieties, Monalu (254.9 c/ha), Rom Star (253.0 c/ha), and Champion (252.0 c/ha) showed the highest productivity. Among the hairless peach varieties, Muyassar (244.4 c/ha), Lyuchak Ranniy (244.2 c/ha), and Shirin Magiz (196.8 c/ha) were the most productive
Keywords: peach; fruit weight; yield per tree